Nurses’ attitudes toward ethical issues in psychiatric inpatient settings - Eren, Nurhan (Nursing ethics, 2014)
Background:Nursing is an occupation that deals with humans and relies upon human relationships. Nursing care, which is an important component of these relationships, involves protection, forbearance, attention, and worry.Objectives:The aim of this study is to evaluate the ethical beliefs of psychiatric nurses and ethical problems encountered.Research Design:The study design was descriptive and cross-sectional.Research context:Methods comprised of a questionnaire administered to psychiatric nurses (n = 202) from five psychiatric hospitals in Istanbul, Turkey, instruction in psychiatric nursing ethics, discussion of reported ethical problems by nursing focus groups, and analysis of questionnaires and reports by academicians with clinical experience.Participants:Participants consist of the nurses who volunteered to take part in the study from the five psychiatric hospitals (n = 202), which were selected with cluster sampling method.Ethical considerations:Written informed consent of each participant was taken prior to the study.Findings:The results indicated that nurses needed additional education in psychiatric ethics. Insufficient personnel, excessive workload, working conditions, lack of supervision, and in-service training were identified as leading to unethical behaviors. Ethical code or nursing care -related problems included (a) neglect, (b) rude/careless behavior, (c) disrespect of patient rights and human dignity, (d) bystander apathy, (e) lack of proper communication, (f) stigmatization, (g) authoritarian attitude/intimidation, (h) physical interventions during restraint, (i) manipulation by reactive emotions, (j) not asking for permission, (k) disrespect of privacy, (l) dishonesty or lack of clarity, (m) exposure to unhealthy physical conditions, and (n) violation of confidence.Discussion:The results indicate that ethical codes of nursing in psychiatric inpatient units are inadequate and standards of care are poor.Conclusion:In order to address those issues, large-scale research needs to be conducted in psychiatric nursing with a focus on case studies and criteria for evaluation of service, and competency and responsibility needs to be established in psychiatric nursing education and practice.